The Effectiveness of Spiderweb Learning Media in Enhancing Hijaiyah Letter Recognition Among Early Childhood Learners - Irmawati (Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2024)
This study investigates the effectiveness of Spiderweb Learning media in improving the ability of early childhood learners to recognize and read Hijaiyah letters. Employing a quasi-experimental design with a non-equivalent control group, this research involved 40 students from Class B at Kindergarten Pertiwi 26-13 Bogares Kidul, who were selected through purposive sampling. The sample was divided into two groups: an experimental group receiving instruction through web Spiderweb Learning media and a control group taught using conventional methods. The research procedure included pre-tests, instructional interventions, and post-tests to assess learning outcomes. Data collection was conducted through direct observation, interviews, and standardized testing, with analysis performed using SPSS version 28. The Mann-Whitney U test results indicated a statistically significant improvement in the experimental group’s performance compared to the control group, confirming the effectiveness of Spiderweb Learning media as an instructional tool. The findings suggest that interactive learning media can enhance early literacy development by providing engaging and structured stimuli. However, limitations such as the short duration of the intervention and the absence of qualitative engagement measures necessitate further research. Future studies should incorporate longitudinal methodologies and mixed-method approaches to evaluate the long-term impact and broader applicability of web-based learning tools in Arabic literacy education. The study contributes to the growing body of research on digital learning interventions and provides valuable insights for educators and policymakers seeking to enhance early childhood Arabic literacy instruction.